The Relationship Between Eating Habits and Gastritis Incidence Among Female Students at Al-Barokah Sruni Islamic Boarding School - Sari, Ines Puspita; Tyastirin, Esti; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2025)
Gastritis is an inflammation of the stomach lining often triggered by unhealthy eating habits or irregular eating patterns. This study aims to analyze the relationship between eating habits (meal frequency, portion sizes, and types of food) and the incidence of gastritis among female students at Al-Barokah Sruni Islamic Boarding School. Poor eating habits, such as irregular meals, consuming overly spicy, fatty foods, or foods containing high caffeine, are known to cause digestive issues, including gastritis. This study uses an observational analytic design with a cross-sectional approach. The sample consists of 55 female students selected using simple random sampling from a population of 65 students. Data were collected from September to October 2024 and analyzed using the Phi coefficient test. The results indicate a significant relationship between meal frequency (ρ-value = 0.001), portion sizes (ρ-value = 0.002), and types of food (ρ-value = 0.004) with the occurrence of gastritis, with each relationship categorized as moderate. Of the total of 55 female students, 24 (43.64%) had gastritis, while 31 (56.36%) did not have gastritis. Based on these findings, it can be concluded that poor eating habits increase the risk of gastritis among the students. It is recommended that the pesantren provide education on healthy eating habits and stress management to prevent the occurrence of gastritis among the students.